2015
DOI: 10.1002/brb3.416
|View full text |Cite
|
Sign up to set email alerts
|

Fatherhood contributes to increased hippocampal spine density and anxiety regulation in California mice

Abstract: IntroductionParenting alters the hippocampus, an area of the brain that undergoes significant experience‐induced plasticity and contributes to emotional regulation. While the relationship between maternal care and hippocampal neuroplasticity has been characterized, the extent to which fatherhood alters the structure and function of the hippocampus is far less understood.MethodsHere, we investigated to what extent fatherhood altered anxiety regulation and dendritic morphology of the hippocampus using the highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…While paternal experience did not significantly alter DG dendritic spine density in the present study, we have previously observed this in California mouse fathers at the time of weaning [34]. Similarly, maternal rodents display increased dendritic spine density within the DG of the hippocampus [18].…”
Section: Discussionsupporting
confidence: 45%
“…While paternal experience did not significantly alter DG dendritic spine density in the present study, we have previously observed this in California mouse fathers at the time of weaning [34]. Similarly, maternal rodents display increased dendritic spine density within the DG of the hippocampus [18].…”
Section: Discussionsupporting
confidence: 45%
“…More recent findings suggest that offspring contact‐induced reductions in anxiety‐like behavior may also be the case in fathers. We have recently observed a decrease in anxiety‐like behavior at PND 19 in California mouse fathers (Glasper et al ., ). Given that the anxiolytic profile, in our present study and prior work, does not develop until ~ 2 weeks post‐birth, it is possible that increased pup retrieval observed at this time point in the California mouse may be directly contributing to our observed effects on emotional regulation.…”
Section: Discussionmentioning
confidence: 97%
“…The California mouse ( Peromyscus californicus ) exhibits extensive paternal care (Gubernick & Alberts, ) that has been well‐characterized (Bester‐Meredith et al ., ), providing a model with which to explore fatherhood‐induced changes in emotional regulation. We recently observed a decrease in PPA‐like behavior on postnatal day (PND) 19 in California mouse males (Glasper et al ., ), a time of reported peak retrievals by fathers of straying pups (Bester‐Meredith et al ., ). However, the extent to which altered anxiety‐like behavior is specific to this time during the postpartum period, and to what extent anxiety‐like behavior is associated with structural changes within the brain, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings were taken from a top-down view at a rate of 30 frames per second. Latency to enter the arms, duration of time spent in the arms, and number of arm entries were assessed as previously described (Glasper et al, 2015 ; Hyer et al, 2016 ). Duration of time spent in the open arms was calculated as total time spent in the open arms divided by the total time spent in both the open and closed arms, excluding the center, multiplied by 100 and presented as a percentage.…”
Section: Methodsmentioning
confidence: 99%